Antibacterial efficacy of silver nanoparticles prepared using Fagonia cretica L. leaf extract. Issue 8 (3rd August 2019) - Bibi, Nausheen; Ali, Qurban; Tanveer, Zafar Iqbal; Rahman, Hazir; Anees, Muhammad
Abstract: Fagonia cretica L. is a known medicinal plant containing important biomolecules. The present study was designed to prepare the silver nanoparticles (AgNP) from F. cretica L. that has never been done before. The AgNP were morphologically characterized using different techniques and their antibacterial activity was also evaluated. The AgNP were crystalline, spherical in shape ranging in size from 20 to 50 nm, and clustered. Different functional groups were detected in AgNP by Fourier transform infrared spectroscopy. Significant antibacterial activities against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Salmonella enterica were observed. The antibacterial activity of AgNP (50 µg) was compared with ciprofloxacin (10 µg) and negative controls producing a larger inhibitory zone than the negative and positive controls in a concentration-dependent manner. It was concluded that the AgNP prepared from F. cretica extract were spherical and aggregated. They were found effective against different clinical isolates of bacteria.